Applications for Induced Pluripotent Stem Cells in Disease Modelling and Drug Development for Heart Diseases - Shu Nakao; Dai Ihara; Koji Hasegawa; Teruhisa Kawamura (European Cardiology Review)
Induced pluripotent stem cells (iPSCs) are derived from reprogrammed somatic cells by the introduction of defined transcription factors. They are characterised by a capacity for self-renewal and pluripotency. Human (h)iPSCs are expected to be used extensively for disease modelling, drug screening and regenerative medicine. Obtaining cardiac tissue from patients with mutations for genetic studies and functional analyses is a highly invasive procedure. In contrast, disease-specific hiPSCs are derived from the somatic cells of patients with specific genetic mutations responsible for disease phenotypes. These disease-specific hiPSCs are a better tool for studies of the pathophysiology and cellular responses to therapeutic agents. This article focuses on the current understanding, limitations and future direction of disease-specific hiPSC-derived cardiomyocytes for further applications.